Implementing and Interpreting Refugee Resettlement Through a Veil of Secrecy: A Case of LGBT Resettlement From Africa - Menetrier, Agathe (Frontiers in Human Dynamics, 2021)
In the last decade the number of countries aiming to resettle refugees increased and complementary pathways aiming to relocate humanitarian migrants expanded. Stakeholders in charge of the selection process of candidates and logistical organization of these programs multiplied as a consequence. Because refugee resettlement and complementary pathways are not entrenched in international law, selection processes and logistical organization are at the discretion of stakeholders in charge, sometimes hardly identifiable themselves, and can vary greatly from one scheme to another. For displaced candidates to resettlement and complementary pathways, this opacity can have dramatic consequences in regions of origin. This article will present the case of a group of African lesbian and gay asylum seekers who first sought asylum in a neighboring country, hoping for resettlement to the global North. Because their first country of asylum criminalizes homosexuality, the responsible regional office of the United Nations High Commissioner for Refugees (UNHCR) must circumvent the said country’s sovereignty on asylum matters and recognize LGBT asylum seekers as refugees under UN mandate before submitting their cases to resettlement countries. UNHCR agents thus conduct refugee status determination (RSD) and resettlement procedures behind a veil of secrecy, at the risk of antagonizing their local partners and confusing aspiring refugees. Meanwhile, INGOs from the global North cooperate with local LGBT associations to relocate LGBT Africans out of the same African countries. This paper will show African asylum seekers’ efforts to qualify for all these programs simultaneously, unaware of the mutually exclusive aspects of some; to become visible to institutions and “sponsors” they deem more powerful, at the expense of solidarity within their group.